Cellular internalization of LiNbO3 nanocrystals for second harmonic imaging and the effects on stem cell differentiation. Issue 14 (22nd March 2016) - Li, Jianhua; Qiu, Jichuan; Guo, Weibo; Wang, Shu; Ma, Baojin; Mou, Xiaoning; Tanes, Michael; Jiang, Huaidong; Liu, Hong
Abstract : Here we report for the first time the use of nonlinear lithium niobate nanocrystals for imaging stem cells via second harmonic generation. Abstract : Second harmonic generation (SHG) nanocrystals have recently been reported to label cancer cells and other functional cell lines due to their unique double-frequency property. In this paper, we report for the first time the use of lithium niobate (LiNbO3, LN) nanocrystals as SHG labels for imaging stem cells. Rat mesenchymal stem cells (rMSCs) were labeled with LN nanocrystals in order to study the cellular internalization of the nanocrystals and the influence on stem cell differentiation. The results showed that LN nanocrystals were endocytosed by the rMSCs and the distribution of the internalized nanoparticles demonstrated a high consistency with the orientation of the actin filaments. Besides, LN-labeled rMSCs showed a concentration-dependent viability. Most importantly, rMSCs labeled with 50 μg per mL of LN nanocrystals retained their ability to differentiate into both osteogenic and adipogenic lineages. The results prove that LN nanocrystals can be used as a cytocompatible, near-infrared (NIR) light driven cell label for long-term imaging, without hindering stem cell differentiation. This work will promote the use of LN nanocrystals to broader applications like deep-tissue tracking, remote drug delivery and stem cell therapy.